Medullary carcinoma of the colon: A comprehensive analysis of the National Cancer Database. (December 2022) - Jabbal, Iktej S.; Nagarajan, Arun; Rivera, Carlos; Yaghi, Marita; Liang, Hong; Nahleh, Zeina; Bejarano, Pablo; Berho, Mariana; Wexner, Steven
Abstract: Purpose: Medullary carcinomas (MC) of the colon are uncommon tumors. In this study, we analyzed demographic and disease characteristics as well as survival outcomes of MC versus undifferentiated (UDA) and poorly differentiated (PDA) adenocarcinomas (AC) of the colon. Materials and methods: The National Cancer Database (2004–2018) was utilized to identify patients with colon cancer. Patient demographics (including age, gender, race), disease characteristics (including grade, TNM stage, carcinoembryonic levels, perineural and lymphovascular invasion, lymph node status, microsatellite stability, KRAS mutation, and primary tumor site), and facility type and location were evaluated. Chi-square tests were used to compare descriptive data. Cox Regression and Kaplan Meier analyses were used to analyze survival characteristics. Results: 1, 041, 753 patients with colon cancer were identified of whom 2709 patients had MC and 897, 902 had AC (136, 597 PDA and 18, 042 UDA). MC was seen in older patients (mean age 74 ± 13 years) and women (72.5% vs. 27.5% males). Most MCs were poorly differentiated (63.3%), and 82.4% of patients with MC had microsatellite instability. Fewer patients with MC had perineural invasion (15.6% vs. 22.0% in PDA and 22.4% in UDA, p < 0.001) and positive lymph nodes (38.4% versus 59.9% with PDA and 59.7% with UDA, p < 0.0001). MC diagnosis increased by year (Cochran-Armitage trend test, p < 0.0001). Kaplan Meir analysis revealed a better prognosis for patients with MC when compared to PDA or UDA (p < 0.001). Conclusion: Given the rarity, pathologists should maintain a high suspicion for MC when encountering poorly differentiated or undifferentiated right-sided colon cancer with associated MSI-H. Highlights: Recognition of medullary carcinoma as a separate clinical has raised awareness, increasing its diagnosis over the years. MC of the colon have distinct clinicopathological characteristics than poorly (PDA) and undifferentiated adenocarcinomas (UDA). Most MCs have a lower propensity for local and distant metastasis, leading to better survival outcomes than PDA/UDA. MC of the large intestine is a rare subset more common in women and the older population. The complexities and similarities of MC to PDA and UDA may lead to the underdiagnoses of this rare but distinct subtype.